Penerapan Pembelajaran Cooperative Learning dengan Teknik Example Non Example untuk Meningkatkan Aktivitas dan Hasil Belajar Peserta Didik di SD Negeri 37 Cakranegara - Gede Lawa, I Dewa (UNDIKMA, 2021)
This study aims to improve the activities and learning outcomes of Class V students at SD Negeri 37 Cakranegara through the application of the example non example cooperative learning technique approach. This research method uses classroom action research which is carried out in two cycles. The research instrument used observation and tests. The data analysis technique used in this research was qualitative and quantitative descriptive analysis. The final results of the action in cycle II showed that the results of teacher observations obtained an average score (4.45) and the results of student observations reached an average score (4.48). While the learning outcomes of students reached an average value (79.14), meaning that the indicators of success (> 75.00) had been exceeded. Because the indicators of success have been proven, this study was declared successful and was stopped in cycle II.